Exploring the use of microbial enhanced oil recovery in Kazakhstan: a review - Yernazarova, Aliya; Shaimerdenova, Ulzhan; Akimbekov, Nuraly; Kaiyrmanova, Gulzhan; Shaken, Muhtar; Izmailova, Asem (Frontiers in Microbiology, 2024)
Microbial enhanced oil recovery (MEOR) is a promising method for improving oil recovery from challenging reservoirs such as those found in Kazakhstan. MEOR relies on the activities of microorganisms to modify the properties of the reservoir, such as reducing the oil viscosity, increasing the reservoir permeability, and generating by-products that mobilize the oil. Implementing MEOR in Kazakhstan could lead to significant economic benefits for the country by increasing oil production and royalties from fossil fuel exports. Oil production in Kazakhstan has seen fluctuations in recent years, with 2018 recording a production level of 1.814 million barrels per day. Among regions, Atyrau region contributed the most to oil production with 23.4 million tons of oil. Following Atyrau, the Mangystau region produced 8.2 million tons, and Aktobe produced 2.4 million tons. Overall, the use of MEOR in Kazakhstan's oil fields could offer a promising solution for enhanced oil recovery, while minimizing environmental impact and cost. While specific data on the current use of MEOR in field conditions in Kazakhstan might be limited, the fact that studies are underway suggests a growing interest in applying this technology in the country's oil fields. It's exciting to think about the potential benefits these studies could bring to Kazakhstan's oil industry once their findings are implemented in field operations. These studies have significant implications for Kazakhstan's oil production in the future.